If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23 + -1x = 2x + 37 Reorder the terms: -23 + -1x = 37 + 2x Solving -23 + -1x = 37 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -23 + -1x + -2x = 37 + 2x + -2x Combine like terms: -1x + -2x = -3x -23 + -3x = 37 + 2x + -2x Combine like terms: 2x + -2x = 0 -23 + -3x = 37 + 0 -23 + -3x = 37 Add '23' to each side of the equation. -23 + 23 + -3x = 37 + 23 Combine like terms: -23 + 23 = 0 0 + -3x = 37 + 23 -3x = 37 + 23 Combine like terms: 37 + 23 = 60 -3x = 60 Divide each side by '-3'. x = -20 Simplifying x = -20
| -6-3(2k+2)=18 | | ln(2250/x)=2.6 | | .33(6x-9)=1.5(4x-5) | | -16(-4)=64 | | -20-7x=-5x+14 | | (2x^2y)dx=(3x^3y^3)dy | | f(x)=4x^4-17x^2-50 | | -20-7x=5x+14 | | 105+9.50x=14.75x+105 | | 2r-3=-3-7r | | -6x^2+23= | | 3(5p-3)=5(p+7) | | 3(5p-3)=5(p+7) | | 12+(7+3)2= | | -6x^2+23= | | 12+(7+3)2= | | 4m+17=-(4-m) | | 5.5=-2 | | h(t)=30t-2t^3 | | w+6=6(w-6) | | 12+(7+32)= | | 9/11/9= | | -4(x+3)=36 | | 7z=72 | | 5x-10/6x-6 | | 10x/12=-28 | | 24n+18=4n-2 | | 7/3x=77/4 | | 4j+6j=8.6 | | -4s-5+6-3s= | | -9-2x=17-x | | 3x+27=4.5x |